Modelling Approaches for Minimally Gauged Sg Similajau, Bintulu - Mah, D.Y.S.; Hii, Ching Poon; Kho, Addy (JASPE, 2017)
Minimally gauged river basins are common in Sarawak. Many river basins are lacking in hydrological monitoring mechanism mostly due to the vast land mass and complex river network, hence causing isolation of certain locations. This paper is describing the approaches to model Sg Similajau of Bintulu, Sarawak with little information to support sound analysis. A river model is developed to reconstruct missing flows of the river. In order to have reliable results, a short-term monitoring program is strongly suggested to collect data pertaining to river processes in the field. Pre-processing processes are demonstrated to obtain inflow data for upstream boundaries, tide/King Tide data for downstream boundary and a weir at Samalaju Water Intake for middle boundary. Particularly the weir, its presence convinces the verification of the river model. Post-processing on the impacts of the weir in flow patterns, in this case the water head produced by the weir and with such a head to flush out saltwater brought about by tides are demonstrated as ideal tool to test the model.